Review on Network Function Virtualization in Information-Centric Networking - Fazea Y.; Mohammed F.; Madi M.; Alkahtani A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Transfer functions; Commodity hardware; Content retrieval; Future challenges; Information-centric networkings; Information-centric networkings (ICN); Network functions; Operating expense; Virtual communication; Network function virtualization